Influence of irrigation and nutrient levels on growth performance and nutrient concentration in khair (Acacia catechu Willd.) plantation under mid hill conditions of Himachal Pradesh - Sharma, Yogender; Sharma, J.C.; Upadhyay, G.P. (Indian Journal of Agroforestry, 2020)
Field experiment was conducted during May 2001 to May 2002 to study the influence of irrigation and nutrient levels on the growth performance of khair (Acacia catechu) plantation (six-year) in the mid hill conditions of Himachal Pradesh. There were nine treatment combinations comprising of three irrigation and three nutrient levels. Results of the study revealed that growth performance (height, collar diameter, current annual increment and above ground biomass) and N, P, and K concentration in leaves increased significantly with the increasing irrigation (IR0 to IR2) and nutrient (NR0 to NR2) levels. Maximum increment in the growth parameter and higher nutrient concentration in leaves were recorded with the treatment combination IR2NR2 (irrigation at 15 days interval and 90, 90 and 60 kg/ha N, P2O5 and K2O) over IR0NR0 (control). The growth parameters registered significant and positive relationship with the soil moisture. On the basis of the results of one year study, it was observed that A. catechu responded favorably to irrigation at 15 days interval and application of 90, 90 and 60 kg/ha N, P2O5 and K2O, respectively. The positive interactive effect of irrigation and nutrients, on height, collar diameter, current annual increment (CAI) and leaf N, P and K concentration promoted the above ground biomass. The study underlined the need that this species needs to be fertilized with 90, 90 and 60 kg/ha N, P2O5 and K2O, Â respectively with irrigation at 15 days interval or at least at monthly interval, to have better growth performance in the initial years of afforestation/plantation.